Konsep Diri Jurnalis Perempuan (Studi Fenomenologi Tentang Pengalaman Traumatik Jurnalis Perempuan Saat Menjalankan Profesinya) - Hidayah, Alifvia Nurul; Malik, Abdul; Putri, Liza Diniarizky (Fakultas Ilmu Komunikasi UKWMS, 2024)
This research aims to understand how female journalists develop their self-concept after experiencing traumatic events while performing their professional duties. Traumatic experiences include incidents such as invasion of privacy, sexual violence, terror, destruction threats, and verbal abuse. The phenomenon examined in this research is the impact of this experience on self-concept and the actions taken to restore the psychological condition of female journalists. A qualitative approach with phenomenological methods and symbolic interaction theory was employed. In this research, researchers involved 5 (five) female journalist informants using snowball sampling techniques. The finding reveal a variety of responses among female journalists, ranging from self-blame and doubt to positive self-concepts achieved by establishing personal boundaries. The essence of female journalists' responses to traumatic experiences obtained from structural descriptions extracted from narrative textural descriptions resulting from participant interviews is that even though they are faced with challenges and trauma, female journalists show resilience, determination, and a willingness to learn and grow from their experiences. which impacts their affirmation of their profession and personal well-being. This research contributes to the literature by providing a new perspective on the psychological dynamics and professionalism of female journalists in a local context. Apart from that, this research also has practical implications for media organization and government policies regarding the protection of female journalists and support for female journalists in various concrete forms. ABSTRAK Penelitian ini bertujuan memahami bagaimana jurnalis perempuan mengembangkan konsep diri mereka setelah mengalami peristiwa traumatis ketika melakukan tugas profesionalnya. Pengalaman traumatis mencakup insiden seperti pelanggaran privasi, kekerasan seksual, teror, ancaman pengrusakan, dan pelecehan verbal. Fenomena yang diteliti dalam penelitian ini adalah dampak pengalaman tersebut pada konsep diri dan tindakan yang dilakukan untuk memulihkan kembali kondisi psikologis jurnalis perempuan. Pendekatan kualitatif dengan metode fenomenologi dan teori interaksi simbolik digunakan. Dalam penelitian ini peneliti melibatkan 5 (lima) orang informan jurnalis perempuan dengan menggunakan teknik snowball sampling. Temuan mengungkapkan beragam respon jurnalis perempuan, mulai dari menyalahkan dan meragukan diri sendiri hingga pengembangan konsep diri yang positif yang dicapai dengan membangun batasan-batasa personal. Adapun esensi dari respon jurnalis perempuan terhadap pengalaman traumatis yang diperoleh dari deskripsi struktural hasil ekstraksi dari deskripsi tekstural narasi hasil wawancara partisipan adalah walaupun dihadapkan pada tantangan dan trauma, para jurnalis perempuan menunjukkan adanya resiliensi, determinasi, dan kesediaan untuk belajar dan tumbuh dari pengalaman mereka, yang berdampak pada afirmasi mereka pada profesi dan kesejahteraan personal. Penelitian ini berkontribusi pada literatur dengan memberikan perspektif baru tentang dinamika psikologis dan profesionalisme jurnalis perempuan dalam konteks lokal. Selain itu, penelitian ini juga berimplikasi praktis bagi kebijakan organisasi media dan pemerintah terkait perlindungan terhadap jurnalis perempuan dan dukungan terhadap jurnalis perempuan dalam berbagai bentuk nyata.